Aesthetic Communication of 'Wiraga Alus Wirasa Tumus': A Semiotic Analysis of Waranggana Representation in the Wara Genjong Dance YouTube Video - Bagus Aditya Susanto; Tito Edy Priandono; Alwan Husni Ramdani (Javanologi: International Journal of Javanese Studies, 2026)
The digitalization of the Wara Genjong dance on YouTube represents a critical transition of local Javanese traditions into global participatory culture. This study aims to analyze the aesthetic communication and digital representation of the waranggana within this virtual space. Employing a qualitative desk research approach, this study applies Roland Barthes' semiotic analysis to decode verbal and visual signs in the high-definition YouTube broadcast of the "Pengantin Nusantara" event by Anjungan Jawa Timur (2021). The findings reveal a profound synthesis of textual lyrics and visual signifiers. The flawless execution of refined movements (wiraga alus) visually embodies spiritual resonance, while the dynamic manipulation of the traditional scarf (sampur diseblak) actively negotiates physical allure and deconstructs passive gender stereotypes. Ultimately, this aesthetic communication successfully reconstructs the waranggana myth, elevating her as a symbol of female bodily autonomy. By blending sacred aesthetics with secular folk traditions, the digital broadcast of the Gembyangan graduation ritual institutionalizes the cultural identity of Ngrajek hamlet (Dusun Ngrajek), located in Sambirejo Village, Tanjunganom District, Nganjuk Regency. In conclusion, digital platforms serve not merely as passive archives, but as active, resilient spaces for preserving intangible cultural heritage.